2019
DOI: 10.1002/cctc.201901872
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Photoelectrochemical Activity of TiO2 Electrodes by Multilayer Screen‐Printing

Abstract: Screen-printing is a commonly used method for the preparation of photoelectrodes. Although previous studies have explored the effect of the number of printed layers on the efficiency of dye-sensitized solar cells, its interplay with the photoelectrocatalytic properties of the electrodes has rarely been examined. This study focuses on this issue by studying the photoelectrocatalytic oxidation of methanol over TiO 2 electrodes. Incident photon-to-current efficiencies reached 87 % at the optimal conditions of mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 57 publications
(72 reference statements)
1
9
1
Order By: Relevance
“…Such highly oxidative power results in the faradaic efficiency around 30 % for methanol oxidation to form formaldehyde [10] . Further formaldehyde oxidation to formic acid on TiO 2 over reaction time was observed in both PEC [5b] and transient absorption [5d] measurements, which is not observed in our study herein using α‐Fe 2 O 3 , indicative of the difference in thermodynamic activation barrier causing different reaction pathway. Our results indicating the thermodynamic and kinetic challenge for the oxidation of organic molecules is further supported by a recent study of oxidation reactions using TiO 2 for complete removal of persistent organic pollutants [3a] .…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…Such highly oxidative power results in the faradaic efficiency around 30 % for methanol oxidation to form formaldehyde [10] . Further formaldehyde oxidation to formic acid on TiO 2 over reaction time was observed in both PEC [5b] and transient absorption [5d] measurements, which is not observed in our study herein using α‐Fe 2 O 3 , indicative of the difference in thermodynamic activation barrier causing different reaction pathway. Our results indicating the thermodynamic and kinetic challenge for the oxidation of organic molecules is further supported by a recent study of oxidation reactions using TiO 2 for complete removal of persistent organic pollutants [3a] .…”
Section: Resultscontrasting
confidence: 62%
“…However, such impressive PEC results were only reported with a few metal oxide materials. For example, hematite (α‐Fe 2 O 3 ) and bismuth vanadate (BiVO 4 ) have been reported as suitable candidates for alcohol oxidation to form aldehyde with >90 % faradaic efficiency, [1a,9] whereas merely 30–60 % of faradaic efficiency of methanol oxidation to formaldehyde using titanium dioxide (TiO 2 ) were reported, [5b,10] clearly indicating that the reaction mechanism differs from materials and this particular challenge has not been significantly considered to date.…”
Section: Introductionmentioning
confidence: 99%
“…These examples have shown the suitability of the model for the fit of transient signals for powdered photocatalysts, but the model can be applied for fitting the signals of photocatalyst films, as well. A recent work showed that the lifetime and the decay constant of screen-printed TiO 2 electrodes depend on the number of printed layers, and thus on the thickness of the films [14]. In Fig.…”
Section: Charge Carrier Recombination Kineticsmentioning
confidence: 93%
“…Thus, the transient signal decays faster for the one-layer electrode compared to the multilayer electrodes. These TiO 2 electrodes are one example where both, the second order model and the fractal kinetics model, are suitable for fitting the transient decays, and they also lead to similar results [14]. However, by fitting with the fractal kinetics model the fractal parameter h is obtained in addition, which is directly related to the surface roughness of the electrodes.…”
Section: Charge Carrier Recombination Kineticsmentioning
confidence: 98%
See 1 more Smart Citation